(untitled) - Cernicky, Lubomir (Doprava a spoje, 2012)
Red-light running is one of the common causes of road traffic accidents. One of the basic measures to reduce it is strict police traffic enforcement. Recently, there is a tendency to change classical police enforcement method into automated camera enforcement method. Such a system is Red Light Violation Detection System.